TheThreeHundred project: backsplash galaxies in simulations of clusters. Issue 4 (3rd February 2020) - Haggar, Roan; Gray, Meghan E; Pearce, Frazer R; Knebe, Alexander; Cui, Weiguang; Mostoghiu, Robert; Yepes, Gustavo
ABSTRACT: In the outer regions of a galaxy cluster, galaxies either may be falling into the cluster for the first time or have already passed through the cluster centre at some point in their past. To investigate these two distinct populations, we utilize TheThreeHundred project, a suite of 324 hydrodynamical resimulations of galaxy clusters. In particular, we study the 'backsplash population' of galaxies: those that have passed within R 200 of the cluster centre at some time in their history, but are now outside of this radius. We find that, on average, over half of all galaxies between R 200 and 2 R 200 from their host at z = 0 are backsplash galaxies, but that this fraction is dependent on the dynamical state of a cluster, as dynamically relaxed clusters have a greater backsplash fraction. We also find that this population is mostly developed at recent times (z ≲ 0.4), and is dependent on the recent history of a cluster. Finally, we show that the dynamical state of a given cluster, and thus the fraction of backsplash galaxies in its outskirts, can be predicted based on observational properties of the cluster.